2009
DOI: 10.1039/b907831b
|View full text |Cite
|
Sign up to set email alerts
|

Exploring synthetic avenues for the effective synthesis of selenium- and tellurium-containing multifunctional redox agents

Abstract: Various human illnesses, including several types of cancer and infectious diseases, are related to changes in the cellular redox homeostasis. During the last decade, several approaches have been explored which employ such disturbed redox balances for the benefit of therapy. Compounds able to modulate the intracellular redox state of cells have been developed, which effectively, yet also selectively, appear to kill cancer cells and a range of pathogenic microorganisms. Among the various agents employed, certain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 27 publications
1
49
0
2
Order By: Relevance
“…Furthermore, we have also shown that the tellurium containing compounds 6 and 5 are generally able to enhance the oxidation of thiols in the presence of H 2 O 2 , using a simple in vitro thiophenol oxidation assay. 11,12 In continuation of our previous work, the ROS levels in (the more robust) A 431 cells were monitored using the standard fluorescent 2`, 7` dichlorodihydrofluorescin diacetate (DCHFA) assay, which can be considered as a general ROS indicator, as DCHFA reacts readily with most common ROS, including H 2 O 2 , lipid hydroperoxides and ONOO − . 17 As suspected, in the concentration range used, sulfur and selenium based compounds were unable to disturb the ROS levels in A 431 melanoma cells over a 1 h treatment period.…”
Section: 3 M E C H a N I S Ti C S Tu D I E Smentioning
confidence: 99%
“…Furthermore, we have also shown that the tellurium containing compounds 6 and 5 are generally able to enhance the oxidation of thiols in the presence of H 2 O 2 , using a simple in vitro thiophenol oxidation assay. 11,12 In continuation of our previous work, the ROS levels in (the more robust) A 431 cells were monitored using the standard fluorescent 2`, 7` dichlorodihydrofluorescin diacetate (DCHFA) assay, which can be considered as a general ROS indicator, as DCHFA reacts readily with most common ROS, including H 2 O 2 , lipid hydroperoxides and ONOO − . 17 As suspected, in the concentration range used, sulfur and selenium based compounds were unable to disturb the ROS levels in A 431 melanoma cells over a 1 h treatment period.…”
Section: 3 M E C H a N I S Ti C S Tu D I E Smentioning
confidence: 99%
“…As before, the IMCR-based approach turned out to be rather successful for the synthesis of a range of chemically diverse sulfur-, selenium-and tellurium-containing peptidomimetic compounds (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). These compounds were tested in various cancer cell lines and, in the case of the tellurium compounds, showed considerable activity in many of these cell cultures, possibly by selectively damaging the ER and actin cytoskeleton, delaying the cell cycle and inducing apoptosis.…”
Section: Resultsmentioning
confidence: 93%
“…11,12 Although the method appears to work well, the scope of the method is rather limited by the accessibility to the isonitrile building block. Chalcogens (sulfur, selenium and tellurium) bearing isonitriles have therefore been synthesized accordingly to overcome this sophisticated limitation.…”
Section: A R T I C L E I N F Omentioning
confidence: 99%
See 1 more Smart Citation
“…A library of cyclic pentapeptides were synthesised as potential antagonists of CXCR4, a member of the G-protein coupled receptor family, which is implicated in many diseases including cancer . Redox catalysts containing selenium and tellurium have been designed and synthesised since compounds with the ability to alter the redox state in cells have potential anti-cancer activity (Mecklenburg et al, 2009). A number of the compounds prepared possess interesting biological activities.…”
Section: Bioactivesmentioning
confidence: 99%